Management of protected areas in Sahel savannah ecoregion of Nigeria under the threat of desertification - BOROKINI Temitope Israel; OJO Abiodun (Scientific Annals of the Danube Delta Institute, 2013)
This study was conducted to assess the challenges facing 8 selected protected areas in the Sahel Savannah ecoregion and proffer solutions to these challenges in order to ensure conservation and sustainability of Nigeria’s biodiversity. Primary data were collected from randomly-selected 120 staffs using questionnaire administration from 8 Forest Reserves within Borno and Yobe states of Nigeria. A high level of encroachment of all the studied protected areas was observed, which ranged from deforestation, overgrazing, poaching to converting protected areas into farmlands. Other notable challenges include poor staffing, inadequate equipment and funding. The respondents further reported that majority of the defaulters were farmers and local people in the area, involved in such practices for their survival in the wake of harsher climate and desert encroachment in the region. This paper calls for a revision of the Government Policy on Forestry in Nigeria to allow the people own and plant forests, implementation of community based forest resources management, provision of environment and user-friendly solar powered cooking stoves and sustainable farming systems such as crop rotation, intercropping, sustainable irrigation, organic farming and agroforestry. In addition, sources of income for the locals need to be diversified, such as honey bee production.